Protecting the Poor Through Programmatic Adjustment Lending in Peru, Brazil and Colombia - Javier, Evangeline; Paqueo, Vicente; Rawlings, Laura B.; Rodriguez, Alberto (World Bank, Washington, DC, 2012)
Social reforms typically require long-term, incremental policy changes. Traditional World Bank (WB) funding for discrete investments or technical assistance often had little broad policy impact. Even sector adjustment loans tended to be too inflexible and short-term to support ongoing social reforms. Some countries needed new kinds of financial and technical assistance to sustain reforms during crisis and beyond. Recognizing the need for steady, incremental reforms combined with institution building, the WB introduced Programmatic Structural Adjustment Loans/Credits (PSAL/PSAC) in 1998. In the social arena, this instrument has provided fast-disbursing, flexible, multi-year support to help countries preserve their social safety nets during crises and strengthen them in the long run through capacity building and institutional reforms. In the Latin America and the Caribbean region, loans to Peru, Brazil, and Colombia illustrate how the new multi-sector social reform efforts have worked in practice.